Huge abdominal and perineal aggressive angiomyxoma: A misdiagnosed case report and literature review - Ma, Jianhua; Wan, Jianghou; Jiang, Bin; Wang, Hua; Zhang, Wei; Zhang, Xiangbo (Cellular and Molecular Biology, 2018)
Aggressive angiomyxoma (AA) is a distinctive soft tissue tumor with a high risk of local recurrence. Clinicians must be aware of this rare tumor pre-operatively. Excision is the preferred method of AA treatment. The case report presents a case of a 36-year-old woman who was difficulty in walking due to a non-painful tumor in the abdomen and perineum. She was misdiagnosed as abdomen neurofibroma for more than 10 years, and an operation was performed in 1997. However, the tumor was incompletely resected because its huge volume accompanies with extensive infiltration and bleeding. The tumors in her abdomen and perineum were growing gradually, and the latter became a large lump which impeded her daily life. In 2008, the perineal tumor was incompletely resected, which weighed 10725 g. The severe hemorrhage had been ceased by Gonadotropin-Releasing Hormone treatment. She is alive till now. Details of the history and operative procedures are presented. An AA diagnosis was made by microscopy immunohistochemically. Long-time misdiagnosis and improper treatment are the important reasons for making it impossible to be radically resected. Pathological and immunohistochemical examination are important for avoiding misdiagnosis. For this case, there is a remaining tumor in her abdomen. A special project including further follow-up and treatment will be taken out.